2010
DOI: 10.1515/revac.2010.29.3-4.233
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Quantification and Antioxidant Activities of Some Pimpinella species

Abstract: In this research, the flavonoid contents of the ethanol and acetone extracts of the aerial parts of Pimpinella rhodantha, Pimpinella tragium subsp. lithophila, Pimpinella cappadocica and Pimpinella kotschyana (Umbelliferae) were determined as rutin and hyperoside, and the antioxidant activity of the ethanolic extracts of these species was studied by using spectrophotometric assays. As a result, the maximum flavonoids containing plant, Pimpinella cappadocica was shown the highest antioxidant activity among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In 1 H NMR spectrum, a singlet at δ 9.32 confirmed the presence of -OH group at C-3 position. [11][12][13][14] .…”
Section: Isolation and Characterization Of A Newmentioning
confidence: 99%
“…In 1 H NMR spectrum, a singlet at δ 9.32 confirmed the presence of -OH group at C-3 position. [11][12][13][14] .…”
Section: Isolation and Characterization Of A Newmentioning
confidence: 99%
“…Pharmacological activity studies revealed that some Pimpinella species have antifungal, antimalarial, antimicrobial, estrogenic (Baser et al 2007), antibacterial (Ates & Erdogrul 2003) and antioxidant (Gülc ın et al 2003;Güvenalp et al 2010) (Tabanca et al 2005), flavonoids (Kuruuzum-Uz et al 2010), terpenoids and steroids (Demirezer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In general, compounds with antioxidant activity have been found to process anticancer, anticardiovascular, antiinflammation, and many other activities 1–3. Flavonoids, which are low‐molecular‐weight benzo‐γ‐pyrone derivatives, are present in both lower and higher plants and form a group of naturally occurring antioxidants 4,5. Flavonoids are increasingly appreciated as being an important component of the human diet.…”
Section: Introductionmentioning
confidence: 99%